2023
DOI: 10.1161/hypertensionaha.122.20434
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Carotid Arteriosclerosis Mediates the Association Between Blood Pressure and Cerebral Small Vessel Disease

Abstract: BACKGROUND: Intracranial arteriosclerosis could explain the association between blood pressure (BP) and cerebral small vessel disease (CSVD). Therefore, we tested whether intracranial carotid artery calcification (ICAC) mediates the association between BP and CSVD and determined pathophysiological mechanisms based on ICAC subtypes. METHODS: One thousand four hundred fifty-eight stroke-free participants from the Rotterdam Study (mean age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…On the other hand, increased pulsatile wave transmission from the aorta to the microcirculation caused by arterial stiffness may also be hazardous to cerebral microvasculature 26 . In line with our findings, a recent study identified that the volume of medial IAC, rather than that of intimal IAC, mediates the association between blood pressure and WMH 27 . These findings indicate that medial IAC, as a proxy for arterial stiffness, may play an independent role in the pathogenesis of CSVD.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, increased pulsatile wave transmission from the aorta to the microcirculation caused by arterial stiffness may also be hazardous to cerebral microvasculature 26 . In line with our findings, a recent study identified that the volume of medial IAC, rather than that of intimal IAC, mediates the association between blood pressure and WMH 27 . These findings indicate that medial IAC, as a proxy for arterial stiffness, may play an independent role in the pathogenesis of CSVD.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that patients with preoperative hypertension had a significantly increased risk of developing PND. Previous studies have reported that hypertension is one of the most important risk factors for the incidence of CVD 22 , and patients with preoperative hypertension have a significantly increased risk of developing postoperative cognitive impairment 23 . Long-term fluctuations in blood pressure can damage the structure of the walls of the cerebral blood vessels and affect the self-regulatory function of cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%